CHANGES IN THE MELIORATIVE STATUS OF MEADOW-ALLUVIAL SOILS IN THE MIDDLE COURSE OF THE ZARAFSHON RIVER DEPENDING ON THE GRANULAMETRIC COMPOSITION - Турсункулова Адиба Бурхоновна (Web of Journals Publishing, 2024)
The article discusses the relationship between the soil's granulometric composition and humus on changes in the physical and meliorative state of the soil. It was found that soils with a heavy mechanical composition have low water carrying capacity and water permeability, and the opposite is true for light mechanical soils. Increasing the amount of humus improves the physical, general-physical, and water-physical properties of both soils with a light mechanical composition and soils with a heavy mechanical composition. Also, the improvement of the land reclamation condition in a positive direction depends on the granulometric composition and the amount of humus, which makes its condition alternative.
Keywords: Zrafshan river, soil, irrigation, salinization, suvli surim, och tusli boz, mechanical composition, analysis.